Music as a Textual Enhancer : A Study of Utitipukkal - Gayathree, S. (University of Jaffna, 2024)
Screen Adaptation is cited as an example of intersemiotic adaptational ultrasemiotic category of translation. Within this dynamic landscape, the shift in sign systems unfolds certain textual enhancers with significant contributions. The resultant target text is embedded with layers of text. Music as a textual enhancer is one of the contemporary challenges in creative arts especially within the context of audio-visual narratives. This study intends to focus on the role of music as a textual enhancer in screen adaptation where the process is across different sets of semiotic signs and with embedded texts. Among various translations from a written text into an audiovisual text in Tamil milieu the translation from Ciṟṟaṉṉai into Utirippūkkaḷ is selected and this study embarks with the novella Ciṟṟaṉṉai and its translation Utirippūkkaḷ as a case study. The study endeavours to unravel the multifaceted role of music as a textual enhancer in the screen adaptation, a category of intersemiotic translation. This study aims to shed light on Music, the underlying text to understand how textual enhancers contribute in the process of intersemiotic translation. The source text and the translation are studied and descriptive method is employed to identify and discuss music as a textual enhancer.
Keywords: Intersemiotic Translation; Screen Adaptation; Textual Enhancer; Music